CULTURAL DIMENSIONS OF COMMUNICATION: INSIGHTS FROM MALAY ENTREPRENEURS IN THE WHOLESALE SME SECTOR OF TERENGGANU - Yusoff, Wan Ahmad Rizal Mohd; Yaacob, Mohd Rafi; Radyi, Siti Amaliya Mohd (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
Communication is central to entrepreneurial success, yet its cultural dimensions remain underexplored within Malaysian small and medium enterprises (SMEs). This paper investigates how Malay entrepreneurs in Terengganu’s wholesale SME sector enact communication shaped by local identity, religion, and social values. A qualitative multiple-case study was conducted through semi-structured interviews with six entrepreneurs, analysed thematically using Atlas.ti. The findings highlight three distinct cultural dimensions—dialect use, Islamic values, and social norms of respect and humility—that frame entrepreneurial communication. These practices integrate emotional intelligence, leadership sensitivity, and cultural authenticity, enabling entrepreneurs to maintain trust, legitimacy, and competitiveness. The study extends communication and competence theories by showing that cultural embedding transforms communication from a transactional skill into a relational, ethical, and strategic resource. Practical implications suggest that SME development agencies should incorporate culturally aware communication training to strengthen resilience and performance.